Study on geometry properties of zeolite and quartz - Lu, Wenlong (2014)
Zeolite and quartz with tetrahedral structure are selected to be researched on their geometrical behaviors under compression mechanism. Template-based geometric simulation is the main method used to model flexible framework structure in this project. I review the background of the selected materials and their framework related applications. I also review the working principle of the selected simulation method. Geometrical properties such as changes of bond length and bond angle due to applied pressure are reported. Furthermore a “flexibility window” of each material is analyzed. Rigid Unit Modes is used to explain the behavior of structure within “flexibility window”. The “flexibility window” of silicate materials is found to be able to vary among different axis of crystal lattice. A relationship between density of material and flexibility window of it is concluded based on testing results. Recommendations for further study on this project are suggested at the end of the report as well.